Başbakanlık Osmanlı Arşivi 168 numaralı mühimme defteri (1183-1185/ 1769-1771): (transkripsiyon, değerlendirme) [s.1-200] - Kırca, Ersin (My University, 2007)
unknown
Keywords: Arşivler_Osmanlı İmparatorluğu 1299-1918; Yeniçağ_Tarih